Life Expectancy in Sub-Sahara Africa: An Examination of Long-Run and Short-Run Effects - Cavusoglu, Behiye; Gimba, Obadiah Jonathan (Asian Development Policy Review, 2021)
The realization of the factors that influence life expectancy is crucial for attaining longevity. In this paper, we examine the long-run and short-run determinants of life expectancy in sub-Saharan Africa (SSA). The determining variables include, inflation, Gross Domestic Product (GDP) per capita, Carbon dioxide (CO2) emission, food production, human capital and health expenditure. The estimation technique used are Pedroni cointegration and pool mean group regression. The results from the Pedroni cointegration show that the variables exhibit long-run relationship. The outcome from the pool mean estimation group confirms that in the long-run inflation and CO2 emission have significantly negative effect on life expectancy while GDP per capita, food production, human capital and health expenditure have a significant and positive influence on life expectancy. It also reveals that in the short-run inflation and food production do not have any impact on life expectancy. The findings recommend that various governments in SSA should increase their public health spending, formulate policies that will discourage CO2 emission and the use of clean energy and food production should be enhanced through modernized agricultural practices.